6gh-15h+10-4g=

Simple and best practice solution for 6gh-15h+10-4g= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6gh-15h+10-4g= equation:


Simplifying
6gh + -15h + 10 + -4g = 0

Reorder the terms:
10 + -4g + 6gh + -15h = 0

Solving
10 + -4g + 6gh + -15h = 0

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -4g + 6gh + -10 + -15h = 0 + -10

Reorder the terms:
10 + -10 + -4g + 6gh + -15h = 0 + -10

Combine like terms: 10 + -10 = 0
0 + -4g + 6gh + -15h = 0 + -10
-4g + 6gh + -15h = 0 + -10

Combine like terms: 0 + -10 = -10
-4g + 6gh + -15h = -10

Add '15h' to each side of the equation.
-4g + 6gh + -15h + 15h = -10 + 15h

Combine like terms: -15h + 15h = 0
-4g + 6gh + 0 = -10 + 15h
-4g + 6gh = -10 + 15h

Reorder the terms:
10 + -4g + 6gh + -15h = -10 + 15h + 10 + -15h

Reorder the terms:
10 + -4g + 6gh + -15h = -10 + 10 + 15h + -15h

Combine like terms: -10 + 10 = 0
10 + -4g + 6gh + -15h = 0 + 15h + -15h
10 + -4g + 6gh + -15h = 15h + -15h

Combine like terms: 15h + -15h = 0
10 + -4g + 6gh + -15h = 0

The solution to this equation could not be determined.

See similar equations:

| 12x-4=13x-5 | | x^3-20x^2+96x=0 | | -x-4x-7=-2x+5 | | -10-3b=3b+2(-8b-5) | | 6g+2gh+5h+15= | | x(x+-6)=40 | | 40=5x-15 | | 8.4m-0.7-8m=0.22 | | 7x+10=2x-10 | | 2gh+5h-20-8g= | | 4(9.7-8.1)=4(9.7)-4(8.1) | | 5/6(9+2x)=40 | | -.5-1=15 | | 2gh-12h-5g+30= | | 12s+8=4s-2 | | .75p-0.6p= | | 4x^2-20x+23=0 | | 3y-7/5=16 | | 8x+15=3x-15 | | 16+x=y | | 2g-5= | | 0.8z+3.74=z+1.5 | | 4(9.7-8.1)=(9.7)-(8.1) | | 75=3-10t-3+6t | | .75(x-5)=12 | | .5x+1=.5x-1 | | .75w-.50w-4=12 | | 8(x+2)=2(4x+4)+8 | | (-3a^2b^3)(-4a^4b^2)= | | 3(t-1)=9+2 | | 596=-8x | | .75(x+5)=12 |

Equations solver categories